2021
DOI: 10.1186/s13287-021-02400-y
|View full text |Cite
|
Sign up to set email alerts
|

BMSC-derived extracellular vesicles intervened the pathogenic changes of scleroderma in mice through miRNAs

Abstract: Background Systemic sclerosis (SSc) is a disease that features severe fibrosis of the skin and lacks effective therapy. Bone marrow mesenchymal stem cell (BMSC)-derived extracellular vesicles (EVs) are potential stem cell-based tools for the treatment of SSc. Methods BMSCs were isolated from the bone marrow of mice and identified with surface markers according to multilineage differentiation. EVs were isolated from the BMSC culture medium by ultrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 59 publications
0
24
0
Order By: Relevance
“…Studies have shown that bone marrow mesenchymal stem cells or adipose mesenchymal stem cells [ 21 ] or their exosomes [ 22 ] achieve good therapeutic effects in the treatment of sclerodermatous mice, but there is no report on HUMSCs-Ex. Almost all cells can release exosomes, but umbilical cord mesenchymal stem cells are cost-effective, productive and acceptable to gain [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that bone marrow mesenchymal stem cells or adipose mesenchymal stem cells [ 21 ] or their exosomes [ 22 ] achieve good therapeutic effects in the treatment of sclerodermatous mice, but there is no report on HUMSCs-Ex. Almost all cells can release exosomes, but umbilical cord mesenchymal stem cells are cost-effective, productive and acceptable to gain [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Raw reads of the library were produced using the Illumina HiSeq 2500 SE50 platform and subjected to an in-house program, ACGT101-miR (LC Sciences, USA), as described previously. 34 High-level miRNAs were filtered according to a higher number of reads than the average copy number of the dataset.…”
Section: Methodsmentioning
confidence: 99%
“…Hematoxylin and eosin (H&E) staining was used to analyze the pathological morphology of corneas as described in our previous study. 34 …”
Section: Methodsmentioning
confidence: 99%
“…BMSCs were maintained in serum-free DMEM for 2 days and then centrifuged at 800 × g and 4°C for 10 min and 10000 × g for 10 min and filtered through a 40 μ m membrane to remove cell debris and dead cells. The supernatant was subjected to ultracentrifugation at 100000 × g and 4°C for 1 h using a SW70Ti rotor (Beckman Coulter Inc., Chaska, MN) [ 26 ]. The extracted pellets were stored at −80°C.…”
Section: Methodsmentioning
confidence: 99%